Space, Scholarship and Skills: building library strategy on new and emerging needs of the academic community - Blake, Michelle; Gallimore, Vanya; Radford, Kirstyn (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
This article follows the publication of a previous article which discussed the outcomes of the Understanding Academics research project (2016-2017) which sought to better understand academic staff at the University of York. The project centred around the use of specific ethnographic methodologies and in particular two UX techniques: cognitive mapping followed by semi-structured interviews. This article focuses on the key themes which emerged from that research and which now underpin the new Library strategy: space, scholarship and skills.